Hydraulic Analysis study and redesign of the water distribution system simulation using GIS- EPANET, case study: Laylan sub-district, Kirkuk city, Iraq - Rashed, Mohamad; Faris, Mariwan; Omar, Najat (Anbar Journal of Engineering Sciences, 2024)
This research project focused on examining and (rehabilitation) redesigning water networks in a city using the GIS-EPANET program in hydraulic network analysis. Due to the availability of outline data about the study area from the municipality's water distribution system (WDS), this study dealt with four cases. From a statistical calculation, the last case was best optimized, which resulted in a high pressure and an acceptable velocity as a result of high mean pressure (13.58) m, logical mean velocity (0.43) m/s, and accurate standard deviations of 1.214 and 0.48 for pressure and velocity, respectively. The study found that the network had a shortfall in pressure, estimated at 40%, due to the lack of expansion to accommodate the growing population. However, after conducting the analysis and identifying the problem, it was found that all regions were receiving adequate amounts of water. Nevertheless, the water speed in the pipelines throughout the network was deficient, below the recommended rate, with a minimum velocity of 0.02 m/s in the pipe (p3) but a minimum pressure of 7.02 m at the junction (607), indicating that the network design was ineffective. Comparing the results obtained with the real-world situation, it was discovered that the network has many violations and disruptions, causing water loss and resulting in low pressure reaching the customers. While the study found that the pressure inside the network was within acceptable modeling limits of (7–12) m, there was a reduction in the pressure charge due to the frequent use of water pumps inside the houses, especially as the circulated area was pumped further away. The error between the model and the real problem may be attributed to water leaks and disruptions from trees, gardens, landscaping, and livestock grazing, as well as the absence of a counter to calculate the water discharge volume to consumers